Analysis of decision making methods in the event of technogenic accidents in real-time management systems (Transport systems and technologies, 2019)
New approaches that allow to expand the logical capabilities of control algorithms based on a thorough analysis of the logic of the decision making process for formalizing the process of object management is considered. Based on the analysis of decision-making methods, it is established that the automation of decision-making processes in the event of emergencies of an anthropogenic nature in the management of forces and facilities should be based on the semiotic principle. To solve the problem of developing solutions in emergency situations of anthropogenic nature, the axiomatic approach is the most acceptable. The development of a method for the synthesis of solution options allows the use of adaptive control algorithms with the modeling of human mental activity. The use of an axiomatic approach to formalizing and solving problems of developing solutions for managing the risks of an industrial accident can only be formalized on the basis of quantitative mathematical methods.
Keywords: modeling, technogenic accident, semiotic system, situational approach, axiomatic approach, synthesis